Penerapan Vidio Animasi Berbasis AI Untuk Meningkatkan Pembelajaran Siswa Kelas 2 MI Miftahul Ulum Kranjingan Jember - M. Ikbal Febriansyah; Imron Fauzi; M. Ilmil Zawawi (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
Learning at the elementary school level requires the use of methods that are interesting, interactive, and appropriate to the development of students. This study aims to evaluate the effectiveness of using artificial intelligence (AI)-based animated videos in improving conceptual understanding and learning motivation of second-grade students at MI Miftahul Ulum Kranjingan, Jember. AI-based learning media was chosen because it is able to present material visually, dynamically, and interactively, making it easier to understand for students who are at the concrete operational development stage. This study used a qualitative approach with data collection techniques in the form of observation of the learning process, interviews with teachers and students, and documentation of classroom activities. The results showed that the use of AI-based animated videos was able to increase students' interest and enthusiasm in participating in learning, clarify their understanding of the material presented, and encourage active participation in discussion activities and exercises. Overall, this study concluded that the application of AI-based animated videos is an effective medium for creating a more interactive, creative, and enjoyable learning process for second-grade elementary school students.